#### Answer

-x, - 2x

#### Work Step by Step

The sum of the terms -x and -2x is -3x.
-x + (-2x) = -x - 2x = -3x

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

-x, - 2x

The sum of the terms -x and -2x is -3x.
-x + (-2x) = -x - 2x = -3x

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.